Analisis Pengetahuan Ibu tentang Pemberian ASI Eksklusif - Darmiati, Darmiati; Arfan, Farmin; Alda, Alda (Yayasan Mandar Indonesia, 2022)
Exclusive breastfeeding means that babies are not given food other than breast milk including water, except for vitamins, minerals and drugs in the form of ORS, drops and syrup. This study used a quantitative research method with a cross sectional design. This research was conducted on all mothers who have babies aged 6 – 24 months who are in Buku Village with a minimum sample of 30 respondents.The results of the study entitled Description of Mother's Knowledge about Exclusive Breastfeeding in Buku Village, Mapilli District which was carried out on 30 breastfeeding mothers, it was found that the average level of knowledge was good, marked by when the study was conducted the majority of respondents were able to answer the questionnaire correctly, namely 18 – 30 years of age with a good level of knowledge related to exclusive breastfeeding, besides that in this study the education level of the majority of respondents was elementary, junior high and high school / vocational education, while the most occupation of respondents in this study was IRT. In addition to age, education and occupation, the number of children in this study also describes the level of knowledge of the respondents. Where in this study the average respondent who has two children has good knowledge about exclusive breastfeeding. The conclusion of this study is that the mother's level of knowledge is on average well marked by when the research was conducted the majority of respondents were able to answer the questionnaire correctly.